BODYWEIGHT CHANGES IN WINTER AND SUMMER CALVING BUFFALO DURING PERIPARTUM PERIOD - ABAYAWANSA, W D; PRABHAKAR, S; SINGH, A K; BRAR, P S (The Indian Journal of Animal Reproduction, 2023)
The present study was conducted on 29 healthy, lactating pleuriparous Murrah buffaloes, in their third to fifthparity and calved during December 2007 to May 2008. The animals were selected at 2 organized dairy farms(Mattewara and Guru Angad Dev Veterinary and Animal Sciences University, Ludhiana). On the basis of season ofcalving they were divided into two group's viz. Winter Calving Buffaloes (WCB) and Summer Calving Buffaloes(SCB). All the calvings were unassisted and the animals had shed their placental membranes. Changes in bodyweightand body condition score (BCS) were recorded at weekly intervals and related to the onset of the ovarian activityfrom calving till 9 weeks (day 63) postpartum. WCB were significantly (P < 0.05) heavier than SCB. Bodyweightloss occurred continuously postpartum throughout the study period. Similarly, BCS was significantly (P < 0.05)higher in WCB than in SCB during the period of study. Body condition also declined continuously in both thegroups during first 63 days postpartum. While WCB lost their body condition by 0.82 points, SCB lost by 0.64points by the end of study period. Loss of BCS after parturition was positively correlated to the onset of ovarianactivity. It can thus be concluded that both the winter and summer calving buffalo lose their bodyweight and BCScontinuously during first 63 days postpartum. Therefore, proper strategy with respect to nutrition should be adoptedto minimize body losses for optimum reproduction and production.
Keywords: Body Condition Score; Bodyweight, Buffalo; Reproduction